2022
DOI: 10.1039/d1cp04716g
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase ion chemistry of titanium–oxofullerene with ligated solvents

Abstract: Gas phase fragmentation events of fullerene-like titanium oxo-cluster anions were investigated in detail. The fragmentation channel of the ions was comparable to the fragmentation of C60 ions with systematic C2 losses which is a consequence of topological similarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Theoretical mass calculations revealed that the crystal consisted of these clusters and a certain number of water and methanol molecules that were derived from the solvent system. Similar solvent-associated peaks were also observed in other metal nanoclusters. The broad isotopic distribution in the mass spectrum can be attributed to two factors: (1) molybdenum (Mo) has seven naturally stable isotopes, resulting in a wide isotopic distribution along with the contributions of naturally abundant isotopes from various atoms i.e., Na, O, S, C, P, and H present in the nanoclusters, and (2) the small mass differences (Δ m ≈ 9–11) between individual nanoclusters in their trianionic state. Additionally, these nanoclusters ionize by getting attached to one or two solvent molecules (H 2 O = 18 and MeOH = 32), which further contributes to the broad distribution of a specific charge state observed.…”
mentioning
confidence: 75%
“…Theoretical mass calculations revealed that the crystal consisted of these clusters and a certain number of water and methanol molecules that were derived from the solvent system. Similar solvent-associated peaks were also observed in other metal nanoclusters. The broad isotopic distribution in the mass spectrum can be attributed to two factors: (1) molybdenum (Mo) has seven naturally stable isotopes, resulting in a wide isotopic distribution along with the contributions of naturally abundant isotopes from various atoms i.e., Na, O, S, C, P, and H present in the nanoclusters, and (2) the small mass differences (Δ m ≈ 9–11) between individual nanoclusters in their trianionic state. Additionally, these nanoclusters ionize by getting attached to one or two solvent molecules (H 2 O = 18 and MeOH = 32), which further contributes to the broad distribution of a specific charge state observed.…”
mentioning
confidence: 75%
“…As a result, mass spectrometry (MS) has been extensively used to study structures and reactivity of cluster ions and supramolecular chemistry of interest, leading to the development of cluster-based materials. [9][10][11][12][13] For example, gas phase dissociation studies of mass-selected clusters through collision induced dissociation (CID) enables the characterization of structures, binding energies, and stability of clusters towards fragmentation. [14][15][16][17][18][19][20] By combining gas phase studies with electronic structure calculations, the intrinsic geometric and electronic structures of clusters may be determined which cannot be obtained using conventional characterization methods.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometric characterization of molecular clusters circumvents some of these challenges. As a result, mass spectrometry (MS) has been extensively used to study structures and reactivity of cluster ions and supramolecular chemistry of interest, leading to the development of cluster-based materials 9 13 . For example, gas-phase dissociation studies of mass-selected clusters through collision-induced dissociation (CID) enable the characterization of structures, binding energies, and stability of clusters towards fragmentation 14 20 .…”
Section: Introductionmentioning
confidence: 99%